GEOWISATA SEBAGAI ALTERNATIF KEGIATAN PASCA TAMBANG PADA LAHAN BEKAS TAMBANG BATU DI KOTA PALANGKA RAYA: Geotourism As An Alternative Post-Mining Activities On Ex-Stone Mining Land In Palangka Raya City - Kristiana, Wita; Tanggara, Deddy Nan Setya Putra (JURNAL TEKNIK PERTAMBANGAN, 2023)
Abstract The use of ex-mining areas for tourism purposes has become a growing trend lately. Geotourism is environmentally responsible tourism by utilizing geological sites or reclaimed ex-mining land areas to be converted into geotourism areas. This activity is expected to bring benefits to the lives of local communities in a sustainable manner. In Palangka Raya, Buhis Hill which is in the Bukit Tangkiling area is an area that used to be a area of quarry mining, in this area the Bukit Cinta Geotourism was developed. This area has a charming landscape,with expanses of meadows, shrubs, and towering rock cliffs. This area also has unique geological features, such as volcanic rocks that form interesting and beautiful geological formations. The Bukit Cinta geotourism area in the Bukit Buhis area has enormous potential to become an ideal place for fans of extreme sports, such as rock climbing, hiking and mountain biking. Buhis Hill also has interesting and challenging hiking trails, which connect several tourist objects in the vicinity. This can be a special attraction for tourists who are looking for an exciting and challenging adventure experience. Keywords: Hills, Tangkiling, Post Mining, Geotourism, Geology